2018
DOI: 10.1038/s41388-018-0203-6
|View full text |Cite|
|
Sign up to set email alerts
|

LncFZD6 initiates Wnt/β-catenin and liver TIC self-renewal through BRG1-mediated FZD6 transcriptional activation

Abstract: Liver tumor-initiating cells (TICs), the drivers for liver tumorigenesis, accounts for liver tumor initiation, metastasis, drug resistance and relapse. Wnt/β-catenin signaling pathway emerges as a critical modulator in liver TIC self-renewal. However, the molecular mechanism of Wnt/β-catenin initiation in liver tumorigenesis and liver TICs is still elusive. Here, we examined the expression pattern of 10 Wnt receptors (FZD1–FZD10), and found only FZD6 is overexpressed along with liver tumorigenesis. What’s more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…According to the existing studies, WNT5A was identified as a non-canonical ligand in Wnt family, with high expression in several human malignancies including GC [44][45][46]. It is noteworthy that WNT5A could activate the β-catenin-mediated Wnt signaling pathway, thereby driving cancerous progression [47]. Furthermore, as described in previous reports, MITF was similarly linked to Wnt/β-catenin signaling pathway [48], which is considered as one of representative target genes of β-catenin [49].…”
Section: Discussionmentioning
confidence: 99%
“…According to the existing studies, WNT5A was identified as a non-canonical ligand in Wnt family, with high expression in several human malignancies including GC [44][45][46]. It is noteworthy that WNT5A could activate the β-catenin-mediated Wnt signaling pathway, thereby driving cancerous progression [47]. Furthermore, as described in previous reports, MITF was similarly linked to Wnt/β-catenin signaling pathway [48], which is considered as one of representative target genes of β-catenin [49].…”
Section: Discussionmentioning
confidence: 99%
“…For example, LncFZD6, which is overexpressed in liver cancer and liver TICs, drives liver TIC self-renewal and tumor initiation capacity. Mechanistically, lncFZD6 directly binds and recruits the BRG1 (Brahma-related Gene 1 protein)-embedded the switch/sucrose non-fermenting (SWI/SNF) complex to the FZD6 promoter, which facilitates the transcription of FZD6 via chromatin remodeling [21]. Similarly, the overexpressed lncHOXA10 recruits the nucleosome remodeling factor (NURF) chromatin remodeling complex to the HOXA10 promoter to initiate the expression of HOXA10, and ultimately promotes the self-renewal of liver TICs and the progression of HCC [22].…”
Section: Lncrnas As Novel Regulators In Hcc Metastasismentioning
confidence: 99%
“…Additionally, a divergent lncRNA of Mitogen-activated protein kinase 6 (MAPK6), called lncMAPK6, is highly expressed along with liver tumorigenesis. It interacts with and recruits RNA polymerase II to be a MAPK6 promoter, and finally activates the transcription of MAPK6 ( Figure 1B) [21].…”
Section: Lncrnas As Novel Regulators In Hcc Metastasismentioning
confidence: 99%
See 2 more Smart Citations